2007
DOI: 10.3184/030823407x218048
|View full text |Cite
|
Sign up to set email alerts
|

Moniline, A New Alkaloid from Dendrobium moniliforme

Abstract: A new alkaloid, moniline (1), and a known alkaloid 6-hydroxynobiline (2) were isolated from the stems and leaves of Dendrobium moniliforme. The structure of 1 was established by spectroscopic methods, especially 2D NMR techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Other major alkaloids, nobiloninetype sesquiterpenoid (C 17 H 27 O 3 N), possess an opened C2-C9 N-heterocycle ring between C2 and N and form a ketone at C-2 (51, 52) (Figure 2F). Moniline (C 18 H 29 NO 4 ) is another alkaloid isolated from D. moniliforme which contains α, β-unsaturated ketone at correlations of H-9/C-10 and H-9/C-8 (53).…”
Section: Alkaloidsmentioning
confidence: 99%
“…Other major alkaloids, nobiloninetype sesquiterpenoid (C 17 H 27 O 3 N), possess an opened C2-C9 N-heterocycle ring between C2 and N and form a ketone at C-2 (51, 52) (Figure 2F). Moniline (C 18 H 29 NO 4 ) is another alkaloid isolated from D. moniliforme which contains α, β-unsaturated ketone at correlations of H-9/C-10 and H-9/C-8 (53).…”
Section: Alkaloidsmentioning
confidence: 99%
“…( Yang et al, 2018 ; Liu et al, 2020 ; Yang et al, 2020 ). In 2007, Liu et al (2007) reported the isolation and structural identification of moniline (50) from the stems and leaves of Dendrobium moniliforme (L.) Sw.. Dendrowardine (51) and wardianumine A (52) were purified from Dendrobium wardianum R. Warner by Liu and Zhao. (2003) and Zhang et al 2017 , respectively.…”
Section: Structural Identification Of Dendrobium Alkaloidsmentioning
confidence: 99%
“…32,123,126,127 6-Hydroxynobiline ( 110) was rst isolated from D. hildebrandii, and its constitution and absolute conguration were conrmed by comparing its spectroscopic data, followed by the transformation of 6-hydroxynobiline (110) into 6-hydroxydendrobine (97). 127 This compound was also found in D. moniliforme 139 and was captured from D. nobile by LC-QTOF-MS. 140 Dihydronobilonine ( 111) was obtained by reduction of nobilonine ( 109) with sodium borohydride 122 and was also isolated from the stems of D. ndlayanum as a natural product. 126 Dendrondline B ( 112), characterised by N-methyl group at C-11, was isolated from the stems of D. ndlayanum and its complete structure was elucidated on the basis of spectroscopic results.…”
Section: Picrotoxane Sesquiterpene Alkaloidsmentioning
confidence: 86%
“…Spectroscopic methods, especially 2D NMR techniques, were used to deduce the structure of moniline (113). 139 Dendrowardine ( 114) is the only N-nobilonium salt present in the fresh plants of D. wardianum. Transformation of dendrowardine ( 114) into dihydronobilonine (111) and spectroscopic analyses helped to determine the structure of dendrowardine (114).…”
Section: Picrotoxane Sesquiterpene Alkaloidsmentioning
confidence: 99%